Testing the Obstacles to Women’s Entrepreneurship Scale (TOWES): Adaptation and Validation of the TOP WOMAN Scale - Ramos, Amparo; Latorre, Felisa; Laguia, Ana (Studia Psychologica, 2026)
Women continue to face gender-related barriers in both accessing leadership positions and becoming entrepreneurs. For this reason, the present study focuses specifically on women to adapt the Testing the Obstacles to Promotion of Women to Management (TOP WOMAN) scale (Ramos et al., 2022), originally designed to measure perceived barriers to access to promotion, and to validate this adapted version, Testing the Obstacles to Women’s Entrepreneurship Scale (TOWES), in the context of entrepreneurship, using a sample of 281 Spanish women. The TOWES presents adequate psychometric properties, comprising a six-factor structure: Motivational/Internal Barriers and Barriers related to Work-family Balance, Gender Stereotypes, Access to Influential Networks, Unequal Opportunities, and Business Culture. The six dimensions showed adequate reliability and construct, concurrent, convergent, and discriminant validity. Unlike the original scale, which consists of seven dimensions, in TOWES the barriers of Unequal Performance Appraisal and Unequal HR Practices are merged into just one. These findings support the validity and theoretical robustness of the adapted scale across different contexts. Moreover, they provide valuable insights for improving campaigns and training programs, identifying barriers to entrepreneurship among women in a specific population, developing objectives for raising awareness among female entrepreneurs, and providing job guidance for women.